2022
DOI: 10.1186/s13065-022-00813-1
|View full text |Cite
|
Sign up to set email alerts
|

Priming with copper-chitosan nanoparticles elicit tolerance against PEG-induced hyperosmotic stress and salinity in wheat

Abstract: In this study Cu-chitosan nanoparticles (Cu-CNP) have been employed as eco-friendly and safer priming agents to induce salt and PEG-induced hyperosmotic stress tolerance in wheat seedlings. Seed priming is a facile on-farm stress management technique that requires a little amount of priming agent and minimizes the eco-toxicological effects on soil fertility. The wheat seeds were primed with 0.12% and 0.16% Cu-CNP for eight hours and were allowed to germinate under normal, PEG-induced hyperosmotic stress (15% P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our findings demonstrated that applying chitosan nanoparticles boosted plant height and biomass. Farooq et al showed that seedlings originating from chitosan nanoparticles treated seeds showed a significant increase in root length under normal conditions [ 30 ] Choudhary et al found that the Cu-chitosan nanoparticles seed treatments improved the shoot length and vigor index of maize seedlings under normal conditions. However, there was no significant effect on the germination percentage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that applying chitosan nanoparticles boosted plant height and biomass. Farooq et al showed that seedlings originating from chitosan nanoparticles treated seeds showed a significant increase in root length under normal conditions [ 30 ] Choudhary et al found that the Cu-chitosan nanoparticles seed treatments improved the shoot length and vigor index of maize seedlings under normal conditions. However, there was no significant effect on the germination percentage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the application of plant-derived nanomaterials (60 ppm) with urea and ammonium sulphate, a significant decrease in enzymatic antioxidants (SOD, POD, and CAT) was observed in both wheat varieties. Farooq et al, [ 66 ] reported that the activity of all the antioxidative enzymes was prolonged in sum at all stages of growth in plants. Alabdallah et al, [ 67 ] reported decrease in the production of SOD, POD, and CAT on crop plants by application of phytogenically prepared metal-based nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress (250, 500 mM NaCl) Salicylic acid mitigated the adverse impacts of salt stress, which decreased flavonoids by enhancing the content of chlorogenic acid [202] Brassica nigra L. Salt stress (100 and 150 mM NaCl) Salinity enhanced forming of many bioactives e.g., phytosterols, and tocopherols [203] Faba bean: Vicia faba L. Salt stress at 150 mM NaCl Salinity induced accumulation of flavonoids, phenols, and tannins, in response to ZnO-NPs [204] Calotropis procera (Aiton) Salt stress in 3 experiments up to 320 mM NaCl using Petri dishes and hydropriming Seed priming with thiourea and ascorbic acid increased tolerance to salinity up to 120 mM by increasing phenolic acids (gallic, caffeic, p-coumaric, p-benzoic, and sinapic acid) [205] Wheat (Triticum aestivum L.) Salt stress (150 mM) Priming with 0.12% Cu-chitosan-NP induced an increase in β-carotenoids, total carotenoids [206] Catharanthus roseus (L.) G. Don Cold stress (4 • C) in growth chamber Decreased alkaloids (vindoline) [207] Glycine max (L.) Merr.…”
Section: Drought Stress (Non-irrigated Field)mentioning
confidence: 99%